OPINI MASYARAKAT KECAMATAN TAMPAN KOTA PEKANBARU TERHADAP ISU JAMAAH SALAFI DI JL. MANYAR SAKTI, PANAM (Studi Kasus Konflik Masyarakat dengan Jamaah Salafi terkait Pembangunan Masjid Abdurrahman bin Auf) - Malfi Sahrin; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
On May 23, 2016, in district tampan of Pekanbaru unrest among Jemaah salafi with locals on Jl. Manyar Sakti, Panam. The conflict arising from the community's displeasure towards the construction of a new mosque in do jemaah salafi. In fact the early emergence of a conflict between the people with the community it's not hot from the construction of the mosque was only, but there are also previous issues or slanted view of society against Jemaah salafi: Jemaah salafi doesn't like the weekly activities of the community such as yasinan, according to yasinan it's not that they are in demand by the Prophet, but that in the recommend is reading surah al kahfi, then open a curtain dividing men and women at a time when religious discourses , its not doing or tahlilan finished prayers, should not be held to celebrate Maulid Nabi Saw and isra ' mihraj, should not do tahlilan after someone had died, according to those who have not done Nabi Saw antiquity then it should not be done or is called bid’ah. This research uses qualitative approach method of the theory of Phenomenology. Data obtained based on the fact that occurred in field through observation, interviews, and documentation. Informants are chosen using a purposive sampling technique, the informants consisted of (religious figures, community leaders, people who live on Jl. Manyar Sakti). Data analysis techniques with the reduction of data, collecting data, presenting data, draw conclusions and evaluation by using the technique of examination validity data that is the extension of participation and triangulation. The results of this research explains that the opinions and attitudes of society towards the issue evolved from the Jemaah Salafi in Jl. Manyar Sakti. The authors conclude that society says the existence of ideology-ideology that evolved but the community does not fully accept, agree and some disagree, then in terms of a conflict that it occurs due to lack of communication so that innocuous actions from the Jemaah Salafi is not acceptable in society. But society is not hating at all of Jemaah Salafi. because fellow Muslims forbidden to mutually hostile.Keywords : Jemaah salafi, Issue, Opinion, Attitude, conflict, Community